Dual-Targeted Therapy in HER2-Overexpressing Breast Cancer with Trastuzumab and Novel Cholesterol-Based Nioplexes Silencing Mcl-1 - Supusson Pengnam; Praneet Opanasopit; Theerasak Rojanarata; Boon-ek Yingyongnarongkul; Chopaka Thongbamrer; Samarwadee Plianwong (MDPI AG, 2023)
The challenge in HER2-overexpressing breast cancer therapy lies in creating an effective target therapy to overcome treatment resistance. Monoclonal antibodies and target gene silencing by siRNA are two potential strategies that have been widely developed for treating HER2-positive breast cancer. The siRNA delivery system is a crucial factor that influences siRNA therapy's success. In this study, lipid-based nanoparticles (cationic niosomes) composed of different cholesterol-based cationic lipids were formulated and characterized for delivering siRNA into HER2-overexpressing breast cancer cells. Niosomes containing a trimethylammonium headgroup showed the highest siRNA delivery efficiency with low toxicity. The myeloid cell leukemia-1 (Mcl-1) siRNA nioplex treatment significantly decreased mRNA expression and breast cancer cell growth. Dual-targeted therapy, consisting of treatment with an Mcl-1 siRNA nioplex and trastuzumab (TZ) solution, noticeably promoted cell-growth inhibition and apoptosis. The synergistic effect of dual therapy was also demonstrated by computer modeling software (CompuSyn version 1.0). These findings suggest that the developed cationic niosomes were effective nanocarriers for siRNA delivery in breast cancer cells. Furthermore, the Mcl-1 nioplex/TZ dual treatment establishes a synergistic outcome that may have the potential to treat HER2-overexpressing breast cancer.